Evaluation of Color and Width of Attached Gingiva Gain in Two Surgical Techniques: Free Gingival Graft and Connective Tissue Graft Covered By Thin Mucosal Flap, a Clinical Trial - Saeed Raoofi; Seyedeh Mohadeseh Asadinejad; Hooman Khorshidi (Shiraz University of Medical Sciences, 2019)
Statement of the Problem: The periodontal health and marginal stability of gingiva can be negatively affected by a number of dental conditions in association with deficiency of attached gingiva. Purpose: This study aimed to compare the color and width of tissue grafted by two surgical techniques of keratinized gingival augmentation, namely free gingival graft(FGG) and connective tissue graft (CTG) covered by thin mucosal flap . Materials and Method: This clinical trial was performed on 15 adult individuals. The patients showed less than 2mm keratinized gingiva on two different recipient sides. One side was to be treated with CTG as the test group and the other side to be treated with FGG as the control group. The amount of keratinized gingiva before the surgery, size of grafted tissue during the surgery and 6 month after the surgery was documented. Six months after healing, the test and control sides were compared in terms of the width of generated gingiva on both sides, and the color match of the grafted areas with the surrounding gingiva or mucosa. The color of the grafted areas was determined and compared by using both professional evaluation and digital evaluation. Results: In digital evaluation, ∆E (which shows color mismatch) was higher in FGG. In professional evaluation, visual analogue scale (VAS) was used by two blinded periodontists. The mean VAS in FGG was less than CTG. The mean increase of gingival width was higher in CTG. The increased width in CTG technique was more than that in FGG technique. This difference was statistically, but not clinically, significant. Conclusion: Higher ∆E in control side and higher mean VAS CTG both showed better color adaptation of CTG side. FGG can be used in case of increasing keratinized gingiva, vestibular depth, and in patients with low smile line without esthetic concerns. However, using connective tissue in the underlying thin mucosal layer is preferred for gingival augmentation if there are adequate vestibule depth and esthetic concerns, like in maxillary canine.